Strategies for Teaching English Vocabulary by Classroom Teachers to Young Learners at SD Alkhairaat - Al Azizah Simangunsong; Ingriyani Yohana Rawung; Sitti Fitriawati Mamudi (Journal of Education Method and Learning Strategy, 2026)
This study aims to describe the strategies used by classroom teachers in teaching English vocabulary to young learners at SD AlKhairaat Poso. The subjects of this research are two classroom teachers who teach first and third grade students, and have no formal educational background in English. This research used descriptive qualitative method, with data collection techniques through classroom observation and interviews. The results of this research showed that:  1) In the first grade, teachers use colored pictures to introduce vocabulary of professions, realia by directly pointing to body parts when the material is about body parts, and mime and gesture to clarify the meaning of words. Teachers also use translation (English to Indonesian), detailed explanations, and presentations that are related to students' lives, such as parents' professions. In addition, teachers compile vocabulary lists (enumeration) and play physical games such as pointing to the mentioned body parts. 2) In the third grade, the teacher uses visual media through projectors and printed books, mimics and gestures, as well as self-composed songs to the tune of children's songs to teach the names of rooms in the school. Teachers also apply translation strategies, explanation of word functions, and ask students to memorize vocabulary through repetition and individual practice. Based on the result obtained, the strategies used by Alkhairaat Elementary School teachers in teaching English vocabulary to Young Learners include: realia, mimic and gesture, picture, translation, explanation, presentation, enumeration, games, and songs. This study contributes to the growing literature on effective strategies for teaching English vocabulary to young learners in classrooms where instruction is provided by non-English teachers. It highlights approaches that can support vocabulary acquisition even in contexts lacking dedicated English language teaching expertise.